DUKUNGAN INDONESIA TERHADAP TIMOR LESTE DALAM UPAYA MENJADI ANGGOTA ASEAN - Seran, Danius Reinaldo; Damayanti, Christy; Haqqi, Halifa (Solidaritas, 2020)
East Timor is the only country in the Southeast Asia region that has not yet joined the regional organization of ASEAN. Application of becoming an ASEAN member has been conducted since 2011. Submission of applications made by Timor Leste must be passed by several requirements and problems to obtain status as a member in ASEAN. As a neighboring country with Indonesia, naturally Indonesia participated in the submission of Timor Leste as a member of ASEAN. Research under the title